Mining genetic loci and candidate genes related to salt tolerance traits in soybean - Rui Tian; Dai Han; Xiaolei Shi; Qimike Shan; Sunlei Ding; Yucheng Wu; Jinbo Zhang; Yongliang Yan (Scientific Reports)
Abstract Soybean is an important crop worldwide that provides ~ 50% oil for humans. Salinity is a major abiotic stress that inhibits soybean growth and yield. Dissecting the genetic basis of salt tolerance is an effective way for soybean plants to combat salt-related yield losses. In this study, the variety salt tolerance index (STIv) of a natural population of 140 soybean germplasms was calculated in terms of plant height (PH), leaf area (LA), shoot fresh weight (SFW) and shoot dry weight (SDW), which were measured under normal condition and in a 1.50% NaCl solution. GWAS analysis was subsequently conducted on the basis of STIv and 150 K SNP markers of “Zhongdouxin-1”. The results revealed that 365 significant SNPs located on 19 chromosomes (excluding Gm03) were associated with STIv. Among them, 108 SNPs were associated with LA-STIv, 71 SNPs associated with PH-STIv, 95 SNPs associated with SDW-STIv and 91 SNPs associated with SFW-STIv. A total of 333 genes were identified according to the flanking region (150 kb) of the significant SNPs. 333 genes were identified. Based on gene functional annotations, SNP mutations, and RNA expressions, nine causal genes responsible for soybean salt tolerance were identified. Thus, the significantly associated SNPs and candidate genes detected in this study might provide novel insights into soybean salt tolerance in breeding programs.